Assessment of Left Ventricular Enlargement at Multidetector Computed Tomography. Issue 5 (September 2015) - Kathiria, Nazima N.; Devcic, Zlatko; Chen, James S.; Naeger, David M.; Hope, Michael D.; Higgins, Charles B.; Ordovas, Karen G.
<x xml:space="preserve">Abstract</x> Purpose Because left ventricular (LV) enlargement (LVE) is indicative of an array of cardiac pathologies, including cardiomyopathic, ischemic, and valvular heart diseases, it is important to recognize it early in the course of these diseases. The recognition of LVE on nongated contrast-enhanced computed tomography (CT) scans should be facilitated by the availability of a dimensional index. To our knowledge, no CT index of LVE has been proposed. Therefore, the study aimed to define whether the maximum LV diameter (LVd) measured on nongated multidetector computed tomography can identify LVE when referencing echocardiography as the diagnostic standard. Materials and Methods The patient population consisted of 438 consecutive patients who had a contrast-enhanced, nongated 16- or 64-detector CT of the chest for evaluation of pulmonary embolism or aortic dissection between January 2006 and March 2008. One hundred fifty-five patients in this group also had an echocardiogram within 2 months of the CT study. The maximum LV cavity size, septal to lateral wall dimension, was measured perpendicularly to the long axis of the left ventricle on the axial CT scans by 2 observers blinded to the echocardiography data. An receiver operating characteristic analysis was performed to identify a highly specific cutoff for the diagnosis of LVE on CT, using echocardiogram as the standard of reference. Interobserver agreement was assessed using Bland-Altman analysis. Results A total of 84 females and 71 males were evaluated (female to male ratio of 1.09). The mean age for the 155 patients was 58 years. Six percent of these patients had a diagnosis of LVE on 2-dimensional echocardiography. The mean (SEM) LV internal diameter at nongated multidetector computed tomography between the group with normal LV and the group with LVE by echocardiography was 4.4 (0.7) cm for the normal LV and 5.9 (1.2) cm for the dilated LVs (P < 0.0001). With the use of threshold value of LVd of 5.6 cm, a sensitivity of 78%, specificity of 100%, positive likelihood ratio of 113.5, and negative likelihood ratio of 0.22 were calculated. The LVd measurements had an excellent agreement between observers on the Bland-Altman analysis. Conclusions Left ventricular enlargement can be reliably identified on nongated contrast-enhanced multidetector CT when the maximum luminal diameter of the LV is greater than 5.6 cm. Nongated contrast-enhanced CT scan can be used to recognize LVE.